Values In Algerian Efl Classrooms: Between Moral Infusion And Moral Autonomy - Ahmed Abdelhakim Hachelaf (Al-Lisaniyyat, 2019)
Moral development focuses on virtuous realization of citizenship. Teachers across disciplines, including EFL play wider education roles. EFL teachers in particular keep juggling between the native and the target culture and often grapple with the issue of morality. The language serves as a vessel for a variety of contexts. The content and skills that English as a foreign language introduces often includes ethical and moral instruction, histories, ideological discourses in addition to controversial social, political, cultural and intellectual issues. In the present paper, we attempt to discuss the problematic issue of teaching morality in the education system with a specific reference to EFL curricula and textbooks. The development of the future/ present citizen involves to a large extent education for values and social norms and the development of manners of a certain type. We coded reference to moral and ethical ends of education in addition to learning materials that include preaching or mention to ethics and morality and mannerism in this category. Our coding resulted in fifty quotations. From content analysis of the Algerian official educational documents, curricula and textbooks, we found out that morality appears extensively in most of the documents of Algerian education policy. One main issue that was discussed is that instruction in the Competency-Based Approach appears tobe problematic. It seems to prepare learners for specified life tasks and socially prescribed roles to be mastered. The school’s mission, then, becomes ‘civilizing’ incompatible groups and poses major power distribution challenge.